A platform for agile virtual enterprise synthesis - Arrais-Castro, Antonio (2012)
Today, competitive pressures require companies to be very fast in introducing new products, to have short production lead times to manufacture and deliver products to customers and to be permanently aligned with the market. Product life-cycles tend to shorten. Even the dynamically reconfigurable global networked structures corresponding to the recent approach of the Agile/ Virtual Enterprise (A/VE) organizational model tend to last a shorter time while becoming more dynamic in their structural reconfiguration. The ability of fast reconfigurability is a requirement that the enterprises corresponding to this A/VE model must satisfy to assure a permanent alignment of the network with the market as highlighted in the paper. The paper defines and discusses the main concepts and features concerning a proposed platform for A/VE synthesis, based on reconfiguration dynamics to help quantify, analyze and manage A/VE, within the context of Ubiquitous Manufacturing System.